Optimisation of the lateral lumbar spine projection using an air-gap technique. Issue 3 (August 2020) - Bellizzi, A.; Zarb, F.
Abstract: Introduction: Lumbar spine radiography is considered as having a high radiation dose compared to other planar radiography examinations. The aim of this study was to investigate the feasibility of replacing an antiscatter grid with an air gap technique to achieve dose reduction for lateral lumbar spine radiography while maintaining image quality on a direct digital radiography (DDR) system. Methods: In phase 1, an experimental study using an anthropomorphic phantom identified the optimal airgap technique. In phase 2, lateral projections of the lumbar spine were performed on 50 patients randomly assigned equally into a control group (using the antiscatter grid) and an experimental group (using the airgap technique). The dose area product (DAP) was recorded, keeping other variables constant. Image quality evaluation was performed by 5 radiologists performing Absolute Visual Grading Analysis (VGA) using an image quality score tool, with resultant scores analysed using Visual Grading Characteristics (VGC). Results: A 10 cm airgap in conjunction with a source to image distance (SID) of 121 cm was found as the optimal airgap technique. The clinical application of this technique resulted in a statistically significant (p < 0.05) reduction in DAP of 72%. Image quality scores were higher for the antiscatter grid but variation between the two techniques was not significant (p > 0.05). Conclusion: Replacing the antiscatter grid with an airgap technique in lateral lumbar spine digital radiography, provides a significant dose reduction whilst still maintaining diagnostic image quality. Implications for practice: The airgap technique is a simple and easy technique to implement and radiographers should find no difficulties in applying it, as It involves no additional cost and no additional equipment.